Finite element modeling for strain rate dependency of fracture resistance in compact bone - Charoenphan S. (2014)
Crack growths in compact bones driven by various strain rate levels were studied using finite element modeling. The energy resistance curves in bovine femur cortical bones were characterized, whereas the orthotropic viscoelasticity in bone materials was accounted for to assess the effect of strain rate on the energy resistance curve. The models were also used to justify the anticipated plane strain response as a result of rather thick specimens used in experiments. Similarities were found between the experimental and model results when crack resistance ability exhibited in bones with slow loading rates, while unstable crack growth existed in bones with rapid loading rates. The critical energy release rates slightly decreased with the increase in strain rates. The hybrid experimental and computational method introduced in this study could be beneficial for application in fracture study in which standard experiments cannot be validly performed. Copyright © 2007 by ASME.